P85 THE SUPERPOWERS OF A REAL HEART TEAM: TAVR AND PERIOPERATIVE MANAGEMENT OF A PATIENT WITH COREA DISORDER. (18th May 2022) - Saccocci, M; Diego, M; Villa, E; Antonio, M; Cirillo, M; Luca, B; Pero, G; Buono, A; Blasi, S; Cuccia, C; Troise, G
Abstract: Aortic stenosis is the most common valve disease in over75 years old patients.Managing the preoperative assessment and the perioperative course could be problematic in frailty patients.Having a real and solid multidisciplinary heart team(MDHT)is essential.This is how we succeeded in optimizing the treatment of 82–year–old patient affected by Huntington's disease(HD) and severe symptomatic aortic valve stenosis.HD is an autosomal–dominant progressive neurodegenerative pathology due to an expanded CAG repeat leading to a mutant protein(huntingtin) and it's usually characterized by chorea, dystonia, incoordination, and cognitive decline.Life expectancy in people with a late manifestation of the disorder can be long, raising the challenge of the treatment of concomitant pathology.Surgery was not indicated in this old and frail patient, but preoperative diagnostic imaging was compulsory to explore the possibility of transcatheter valve implantation. Chorea unintentional movements and dystonia make standard CTscan and angiographic analysis impossible.At our weekly institutional MDHT, we decided to overcome the technical difficulties putting the patient under general anesthesia. As we all know, multiple or very long sedations can be detrimental in frail patients.Confident in our solid multidisciplinary collaboration, we decided on an all–in–one procedure.On the procedure day, the patient was transferred to the hybrid OR.An anesthesiologist and a dedicated nurse induced the patient to general anesthesia.Intubated and with complete vital sign monitoring, the patient was moved back and forth to radiology to perform the angioCTscan.A cardiac surgeon and an interventional cardiologist analyzed the CT images deciding on a transfemoral 34mm Medtronic Evolut Pro+ bioprosthesis. The coronary angiography was performed with no evidence of significant stenosis. We proceed to commissural alignment and release of the bioprosthesis. The patient was extubated in the OR. Stable neurological status, total anesthesia time 140min. The patient was safely discharged home on the second postoperative day. Treating complex cases require multiple skills, well–established protocol, strong communication, and routine cooperation between all the involved professional figures. Therefore, the multidisciplinary heart team is not just an overused word without real significant;it is the only way to approach cardiovascular pathology in our everyday practice permitting us to have a real patient–centered vision.